Neumotórax en el recién nacido. Algunas consideraciones. - Tudela, José M.; Aldama, Laura; Carreras, Alicia; Carro, Gustavo; Fernández, Félix Andrés (Revista Cubana de Pediatría, 2024)
Conocer el comportamiento de esta enfermedad